Expresión artística y pre escritura en niños de Preparatoria Escuela de Educación Inicial y Básica Estancia Pekes ciudad de Loja período 2023 - 2024 - Galvez Sanchez, Britney Fernanda (2024)
Prewriting is the training of traits that include tracing activities, drawing that the child must follow to acquire a clear and legible process when beginning the writing stage and the development of communication strategies before starting to write. The purpose of the research is to determine how artistic expression influences pre-writing in high school children, Estancia Pekes Initial and Basic Education School, city of Loja. The study was framed in a mixed approach by investigating, analyzing and collecting information, both qualitative and quantitative; A descriptive scope was also determined that facilitated and evidenced the characteristics of the children in their natural environment; In its development, inductive-deductive methods were used, which facilitated an analysis and contrast of the results obtained; and, the analytical-synthetic, allowed verifying the problems of pre-writing, and choosing the main information contributing to the construction of the theoretical framework; As an instrument, the assessment scale based on the dimensions of prewriting was applied, denoting in the initial results that 64% of the children presented difficulties in this area; By applying activities based on artistic expression and at the end of the intervention, it was verified that 86% of those investigated reached a high level in the writing process. Concluding that artistic expression is the means by which the child manifests his creativity, being an art, an ideal complement to externalize all emotions and feelings, in addition, it is an effective tool in strengthening pre-writing, which contributes to a greater mastery at a motor, perceptual and intellectual level, allowing the child to demonstrate maturity and independence when entering the most complex writing process. Keywords: Creativity, hand-eye coordination, motor domain, artistic procedures, writing process.